A Pilot Study On The A118g Mu Opioid Receptor Polymorphism Among Drug Addicts In Malaysia - Nagaya, Devaki (2010)

(untitled)
Drug addiction is an important social problem in many countries. Genetic and environmental factors contribute to the predisposition of drug addiction. The opioidergic hypothesis suggests an association between genetic variations at the opioid receptor mu 1 (OPRM1) gene locus and opiate addiction. The present study aim to delineate the frequency of these variants in subjects of Malaysian origin and study their association with the phenotype of opioid dependence together with environmental factors. A118G allele of OPRM1 gene locus was genotyped by using allele specific PCR. The frequency of A allele and G allele was 51% and 49% respectively for addicts and about 73% and 27% respectively for healthy volunteers. The frequency of G allele was 1.77 fold higher in addicts by odds ratio calculation at Cl 95%, which indicate the G allele to be strongly associated with addiction ( X2 =15.31 P< 0.0001; odds ratio 2.51; Cl 95% (1.575 – 3.994), compared to healthy volunteers. A significant association was observed between A118G polymorphism in Opioid receptor gene and drug addiction. The demographic data analysis showed that the majority of the addicts grew up in the environment which makes them prone to addiction. Hence it can be deduced that the genetic and environmental factors play important roles in the development of addiction among Malaysian population.